Pengaruh Sikap Kerja Terhadap Kinerja Karyawan Pada Pt. Duta Marga Silima Di Jakarta - Meily Margaretha; Natalia NATALIA (Jurnal Manajemen dan Bisnis, 2012)
Problems of PT. Duta Marga Silima in Jakarta is that employees often face problems in the work environment, both with colleagues, superiors or with the work itself. Employee attitudesin response to the work environment will be able to influence the performance of employees. The employee attitude there are three kind of employee attitude, that is job satisfaction,organizational commitment and job involvement. The purpose of this research was to determine the influence of work attitudes including job satisfaction, organizational commitment, and work engagement to employee performance at PT. Duta Marga Silima in Jakarta. Based on the Simple Linear Regression Test by using SPPS program version 14.00,job satisfaction coefficient B = 1.534, at ρ = 0.000 <0.05 with determination R ² = 0.409 (40.9%); organizational commitment coefficient B = 0.774, the ρ = 0.000 <0.05 withdetermination R ² = 0.453 (45.3%), and job involvement coefficient B = 0.774, and ρ = 0.000 <0.05 with determination R ² = 0.424 (42.4%). It can be concluded that job satisfaction,organizational commitment, and job involvement have significant and positive impact on employee performance, and the hypothesis that job satisfaction, organizational commitment, and job involvement have significant and positive impact on the performance of employees at PT. Duta Marga Silima in Jakarta is true and acceptable.